Metabolic Adaptions/Reprogramming in Islet Beta-Cells in Response to Physiological Stimulators-What Are the Consequences - Philip Newsholme; Jordan Rowlands; Roselyn Rose'Meyer; Vinicius Cruzat (MDPI AG, 2022)
Irreversible pancreatic β-cell damage may be a result of chronic exposure to supraphysiological glucose or lipid concentrations or chronic exposure to therapeutic anti-diabetic drugs. The β-cells are able to respond to blood glucose in a narrow concentration range and release insulin in response, following activation of metabolic pathways such as glycolysis and the TCA cycle. The β-cell cannot protect itself from glucose toxicity by blocking glucose uptake, but indeed relies on alternative metabolic protection mechanisms to avoid dysfunction and death. Alteration of normal metabolic pathway function occurs as a counter regulatory response to high nutrient, inflammatory factor, hormone or therapeutic drug concentrations. Metabolic reprogramming is a term widely used to describe a change in regulation of various metabolic enzymes and transporters, usually associated with cell growth and proliferation and may involve reshaping epigenetic responses, in particular the acetylation and methylation of histone proteins and DNA. Other metabolic modifications such as Malonylation, Succinylation, Hydroxybutyrylation, ADP-ribosylation, and Lactylation, may impact regulatory processes, many of which need to be investigated in detail to contribute to current advances in metabolism. By describing multiple mechanisms of metabolic adaption that are available to the β-cell across its lifespan, we hope to identify sites for metabolic reprogramming mechanisms, most of which are incompletely described or understood. Many of these mechanisms are related to prominent antioxidant responses. Here, we have attempted to describe the key β-cell metabolic adaptions and changes which are required for survival and function in various physiological, pathological and pharmacological conditions.